Assessment On Transit Oriented Development Pondok Cina According to GBCI - Ria Ayu Rahmawati; R. Agus Murdiyoto (POLITEKNIK NEGERI JAKARTA, 2021)
TOD is designed for public transport passengers and pedestrians to provide comfort and safety in creating a healthy lifestyle. Green Building Council Indonesia (GBCI) is needed as a reference and assessment to optimize building design. The purpose of this paper is to determine the extent of the green building concept applied, calculate the met and unmet Greenship criteria, also measure the GBCI Greenship predicate obtained. The data collection method used is project data and data analysis with the index scale method on Greenship New Building version 1.2. The results showed that in Appropriate Land Use categories credit are 11 points of 17 maximum points with percentage 64,71%, the Efficiency and Energy Conservation categories credit is 1 point of 26 maximum points with percentage 3,85%, the Water Conservation categories credit are 9 points of 21 maximum points with percentage 42,86%, the Source and Material Cycle categories credit are 2 points of 2 maximum points with percentage 100%, the Health and Safety Space categories credit are 4 points of 5 maximum points with percentage 80%, and the Building Environmental Management categories credit are 4 points of 6 maximum points with percentage 66,67%. The final results of TOD Pondok Cina Project are 31 points of 77 maximum points with percentage 40,26% which categorized as Building with Bronze predicate.